A cidade flutuante : espaços, deslocamentos e identidades na literatura pós-moderna - Pizzol, Rafaela Scardino Lima (2008)
The city imposes to its inhabitants an endless movement, a displacement through spaces that do not show any signs of permanence — may it be identity, physical or urban. The urban text is made of constantly moving bodies that write it, many times, without ever getting to read it. In Paul Auster’s novels, and also in several contemporary novels, in a similar way, the characters only possibility of knowing the city comes from their walkings and the narration of what they experiment and testify. In their wanderings, they move through both subjective and empirical structures, as well as words, in an attempt to give shape to the city space and to the absence of any feeling of pertaining. This essay approaches how the urban structures and the contemporary wandering and subjectivity processes are literarily structured, taking as a guideline Paul Auster’s oeuvres, especially the narratives In the country of last things and City of glass, and, in a minor focus, other contemporary novels. In this conceptual panorama, we will discuss and analyze, therefore, the configurations of the contemporaneity in order to study postmodern subjective representations, their relation to the spacial organizations, the identity flotations and the wanderings in the urban space/time, as well as the ways those relations are composed in the postmodern literature.